Academic self-efficacy, perfectionism, and perceived social support as predictors on academic procrastination among e-learning undergraduates in Malaysia during COVID-19 pandemic. - Chee, Vane Yen; Foong, Kar Whey; Tay, Xiao Ying (2021)
The latest ongoing outbreak of the respiratory disease, COVID-19 brings global health in danger. Every university has taken action to transfer the physical learning mode to online learning mode to ensure education continuity. Thus, the current study was a cross sectional study aimed to investigate the predictive effect of academic self-efficacy, perceived social support and perfectionism (adaptive and maladaptive) on academic procrastination among e-learning undergraduates in Malaysia during COVID-19 pandemic. Social Cognitive Theory was used as the theoretical framework in the current study. A total of 177 participants were recruited by using purposive sampling method in which questionnaires were distributed via online platforms such as Facebook, WhatsApp and Instagram. 57.1% of the participants were females while 24.9% were males. 13% of them were Malays, 72.9% were Chinese, 12.4% were Indian and the remaining 1.7% were Kadazan and Melanau or Kanau. The instruments that were implemented in the current study were Level of Academic Self-Efficacy, Multidimensional Scale of Perceived Social Support (MSPSS), Almost Perfect Scale-Revised (APS-R) and Academic Procrastination Scale–Short Form (APS-S). The findings indicated that academic self-efficacy and adaptive perfectionism negatively predict academic procrastination while perceived social support and maladaptive perfectionism positively predict academic procrastination. The present study contributed more information and direction for the future studies to explore in the relevant topic. Relevant parties may also make use of the knowledge and information provided to implement effective and useful strategies to hinder the occurrence of academic procrastination.